Developmental Changes of the Ovary in Neonatal Cotton Rat (Sigmodon hispidus) - Islam, Md. Rashedul; Ichii, Osamu; Nakamura, Teppei; Irie, Takao; Masum, Md. Abdul; Otani, Yuki; Namba, Takashi; Chuluunbaatar, Tsolmon; Elewa, Yaser Hosny Ali; Kon, Yasuhiro (Frontiers in Physiology, 2021)
The reproductive characteristics and ovarian development in cotton rats (Sigmodon hispidus, CRs) are unclear, although CRs are commonly used as animal models in biomedical research. We previously reported that young (6-8 weeks) CRs showed multi-oocyte follicles (MOFs) and double nucleated oocytes (DNOs) in different stages of follicles. The developmental changes in neonatal CR ovaries were investigated in the present study and were compared with our findings in previous studies of unique phenotypes, particularly in oocytes. CR ovaries at postnatal days (PND) 0, 4, and 7 were obtained from the Hokkaido Institute of Public Health. Samples were analyzed by light and transmission electron microscopy. The general histology and folliculogenesis in CR ovaries were similar to those in other experimental rodents. However, DNOs were observed in all age categories and were frequently observed in primordial follicles, whereas MOFs started to develop from PND4 with greater frequency in primary follicles. Almost all developing follicles expressed DEAD (Asp-Glu-Ala-Asp) box polypeptide 4 and forkhead box L2, which are representative markers of oocytes and follicular epithelial cells, respectively. Ki-67 staining demonstrated the proliferative activity of granulosa cells, but not of oocytes, in follicles. Moreover, rapid folliculogenesis of CR due to a small number of apoptotic oocytes was suggested, based on results of the terminal deoxynucleotidyl transferase dUTP nick end labeling assay, confirming the formation of DNOs or MOFs. These findings clarify the development of unique phenotypes of neonatal CR ovaries and support it as a useful model to better understand folliculogenesis and oocytogenesis as well as their abnormalities in humans and other animals.